PCR-RFLP TECHNIQUE FOR SPECIES ORIGIN IDENTIFICATION OF IMPORTED BUFFALO MEAT - Dilger Khdr; Kamaran Taha; Azad Sabow (Mesopotamia Journal of Agriculture)
The study aimed to identify the species origin of imported buffalo meat from three countries Ukraine, Brazil and India to Erbil using PCR-RFLP technique. The pair of universal cyt b primer was designed to amplify a 359 bp DNA fragment in PCR amplification. Then the amplified fragments were digested with Hinf1 and Rsa I restriction enzymes, achieving a characteristics banding pattern in a 2% agarose which produced evidence to identify origin meat species. The results presented that digestion of samples with the Hinf1 RE, produced two bands in each (Ukraine and Brazil), (58 and 301) bp while it was showed different bands in Indian buffalo meat (85, 274) bp. On the other hand the outcomes in the Rsa I RE were two bands in Ukraine and Brazil (156, 203) bp and two bands were obtained in Indian buffalo meat (106, 253) bp. The results realized that the Indian buffalo meat species was not acceptable and showed mislabeling products. Thus, the obtained results recommend that the PCR-RFLP technique with HinfI and Rsa I restriction enzymes play an important role to detect the origin meat species, since it is a fast, simple and easily handle technique for detection of meat species.